2021
DOI: 10.3389/fendo.2021.637317
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Profiles of Chinese Women With Perimenopausal Obesity Explored by the Untargeted Metabolomics Approach

Abstract: By far, no study has focused on observing the metabolomic profiles in perimenopause-related obesity. This study attempted to identify the metabolic characteristics of subjects with perimenopause obesity (PO). Thirty-nine perimenopausal Chinese women, 21 with PO and 18 without obesity (PN), were recruited in this study. A conventional ultra-high-performance liquid chromatography-quadrupole time-of-flight/mass spectrometry (UHPLC-QTOF/MS) followed by principal component analysis (PCA) and orthogonal partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous study had indicated that some substances were easily detected in positive mode, whereas others were easily in negative mode ( Ding et al, 2021 ). To expand the possibility of identification and determination of the metabolites in the samples, a combination of positive mode and negative mode was used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study had indicated that some substances were easily detected in positive mode, whereas others were easily in negative mode ( Ding et al, 2021 ). To expand the possibility of identification and determination of the metabolites in the samples, a combination of positive mode and negative mode was used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Result processing was done according to previous publication ( 24 ). To process the raw data, the ProteoWizard software was used to transform it to mzXML format.…”
Section: Methodsmentioning
confidence: 99%